2014
DOI: 10.1016/j.mjafi.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Women empowerment and use of contraception

Abstract: CI 6.29, 11.98) scoring above 7 (high level of autonomy). In the study population it was found that 273 (70.7%, 95% CI 66.2, 75.28) of the respondents were using contraceptives. Women's autonomy, years of marriage and number of children were significant variables.ª 2014, Armed Forces Medical Services (AFMS). All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 4 publications
8
24
0
1
Order By: Relevance
“…In line with the theoretical framework, it has been evident that women empowerment contributes to high possibility of contraceptive use in Ghana. This is in line with an observation made in India where it was found that women are more likely to use contraceptives when their decision-making competency on their health is not compromised [36].…”
Section: Discussionsupporting
confidence: 91%
“…In line with the theoretical framework, it has been evident that women empowerment contributes to high possibility of contraceptive use in Ghana. This is in line with an observation made in India where it was found that women are more likely to use contraceptives when their decision-making competency on their health is not compromised [36].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, if they have high bargaining power, and therefore a strong ability to influence decision-making in the desired direction, the likelihood that they will use contraception will be high. This outcome is similar to that found by Rwenge (2003); Klomegah (2006) and Patrikar et al (2014). On the other hand, it is far from those of DeRose & Ezeh (2010) who found that the decision-making power of the woman (at the individual level) has no effect on the use of contraception in Uganda.…”
Section: Probit Model Resultssupporting
confidence: 86%
“…A large and growing body of literature has investigated the association between women's empowerment and fertility preferences (Abadian, 1996;Larsen and Hollos, 2003;Patrikar et al, 2014;Al Riyami et al, 2004;Schuler et al, 1996;Upadhyay and Karasek, 2012;and Upadhyay et al, 2014). Fertility preferences are mainly influenced by women's resource control, freedom of movement and freedom from household domination.…”
Section: Some Major Theories On Women's Empowermentmentioning
confidence: 99%
“…While some of this focuses on spill-over benefits resulting from allowing women to have greater control over resources and the impact that this has on the health and education of their children and on better well-being prospects for future generations (the World Bank Poverty, Inequality and Gender Group, 2012), other literature pays particular attention to the relationship between women's empowerment and health outcomes (see, for example, Abadian, 1996;Bloom et al, 2001;Fotso et al, 2008;Larsen and Hollos, 2003;Lee-Rife, 2010;Patrikar et al, 2014;Wypij and Gupta, 2001;Sado et al, 2014;Schuler et al, 1996;Schuler et al, 1997;Upadhyay and Karasek, 2012;and Upadhyay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%